Effects of Physical Activity on Quality of Life, Anxiety and Depression in Breast Cancer Survivors: A Systematic Review and Meta-analysis - Mengying Sun; Chunlei Liu; Yanjuan Lu; Fei Zhu; Huanxi Li; Qian Lu (Elsevier, 2023)
Summary: Purpose: Anxiety, depression, and poor quality of life (QOL) were considered important concerns that hindered the rehabilitation of breast cancer survivors. A number of studies have investigated the effects of physical activity, but they have not reached the same conclusions. This review aimed to identify the effects of physical activity on QOL, anxiety, and depression in breast cancer survivors. Methods: PubMed, Embase, Web of Science, Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycINFO, SinoMed, CNKI, Vip, and WanFang databases were searched for the time period between January 1, 2012, and April 30, 2022. Studies were included if they were randomized controlled trials of the effects of physical activity on QOL, anxiety, or depression in breast cancer survivors. The tools of the Joanna Briggs Institute were used to assess the quality of the included studies. R software version 4.3.1 was used for meta-analysis. Results: A total of 26 studies, involving 2105 participants, were included in the systematic review. Among these, 20 studies involving 1228 participants were included in the meta-analysis. Compared with the control group, the results indicated that physical activity can significantly improve QOL(Hedges' g = 0.67; 95% CI 0.41-0.92) and reduce anxiety (Hedges' g = −0.28; 95% CI −0.46 to −0.10) in breast cancer survivors. However, the effect of physical activity on depression (Hedges' g = −0.46; 95% CI −0.99 to 0.06) was not statistically significant. Conclusions: Physical activity was an effective intervention to improve QOL and reduce anxiety in breast cancer survivors, as well as showed positive trends in depression, although without statistical significance. More well-designed studies are required to clarify the effects of different types of physical activities on the QOL, anxiety, and depression among breast cancer survivors. Registered number on PROSPERO: CRD42022363094.https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=363094.